Claudin-5: A Pharmacological Target to Modify the Permeability of the Blood-Brain Barrier - Campbell, Matthew (My University, 2021)
Claudin-5 is the dominant tight junction protein in brain endothelial cells and exclusively limits the paracellular permeability of molecules larger than 400Da across the blood–brain barrier (BBB). Its pathological impairment or sustained down-regulation has been shown to lead to the progression of psychiatric and neurological disorders, whereas its expression under physiological conditions prevents the passage of drugs across the BBB. While claudin-5 enhancers could potentially act as vascular stabilizers to treat neurological diseases, claudin-5 inhibitors could function as delivery systems to enhance the brain uptake of hydrophilic small-molecular-weight drugs. Therefore, the effects of claudin-5 manipulation on modulating the BBB in different neurological diseases requires further examination. To manipulate claudin-5 expression levels and function, several claudin-5 modulating molecules have been developed. In this review, we first describe the molecular, cellular and pathological aspects of claudin-5 to highlight the mechanisms of claudin-5 enhancers/inhibitors. We then discuss recently developed claudin-5 enhancers/inhibitors and new methods to discover these molecules.
PUBLISHED
Keywords: Claudin-5; Blood–brain barrier; Drug delivery system; Tight junction; Vascular stabilization